INTEGRATED WATER-ENERGY-CARBON NEXUS: A MIXED-METHODS APPROACH TO EVALUATING HILLY RUNOFF POTENTIAL IN UNLOCKING A SUSTAINABLE FUTURE - Shahidul, Islam; Adzlan, A. F. K.; Hishammudin Afifi, Huspi (International Lahore, Pakistan, 2025)
This study evaluates the potential of harnessing renewable energy and producing clean water from hilly runoff resources in Sarawak, with the overarching aim of contributing to a sustainable green future. A mixed-methods approach was adopted, combining field experiments, an extensive literature review, and policy analysis. The findings indicate that Sarawak’s current water demand of 2,060 million litres per day (MLD) could be fully met through hilly runoff, which has an estimated clean water potential of 8,000 MLD and an associated in-Stream Energy capacity of 4.3 MW. Experimental trials conducted in Lundu confirmed that clean water can be produced without chemical dosing or carbon emissions, requiring only 0.55 kWh/m³ of renewable hydropower and thereby reducing emissions by 0.35 kg CO₂eq/m³. The adoption of such a system could prevent approximately 793.1 tonnes of monthly sludge discharge, eliminate chemical use at a rate of 10 mg/L of water, and deliver substantial savings in public health and environmental management costs. Despite these advantages, policy gaps and limited technical capacity in implementing green technologies remain significant barriers. Overall, the study concludes that hilly runoff represents a viable and sustainable pathway towards water and energy security in Sarawak, provided that regulatory frameworks and technological constraints are effectively addressed.